Maisy Goes to the Dentist - Cousins,Lucy (London, Walker Books Ltd, 2023)
Oh no, Charley has a wobbly tooth! Luckily Maisy and friends are on hand to reassure him as he visits the dentist for the very first time. Come along as Charley meets Dr Biteright, takes a twirl on a special chair, has his teeth photographed by an x-ray machine and gargles mouthwash! With a tooth-brushing demonstration and a book to take home, Maisy and Charley learn all about their teeth and how to look after them. Charley is soon smiling again!
Keywords: Picture book fiction